2021
DOI: 10.1038/s41598-021-82077-8
|View full text |Cite
|
Sign up to set email alerts
|

Computer modeling of whole-cell voltage-clamp analyses to delineate guidelines for good practice of manual and automated patch-clamp

Abstract: The patch-clamp technique and more recently the high throughput patch-clamp technique have contributed to major advances in the characterization of ion channels. However, the whole-cell voltage-clamp technique presents certain limits that need to be considered for robust data generation. One major caveat is that increasing current amplitude profoundly impacts the accuracy of the biophysical analyses of macroscopic ion currents under study. Using mathematical kinetic models of a cardiac voltage-gated sodium cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 15 publications
(14 reference statements)
2
23
0
Order By: Relevance
“…While the effects of experimental artefacts in single-cell studies are well-established, consideration of them while building ion channel and action potential models has been limited (Whittaker et al, 2020). In silico studies investigating series resistance effects on voltage clamp recordings have been done in fast-activating currents, such as I Na and I to (Ebihara and Johnson, 1980; Montnach et al, 2021), but to our knowledge artefact equations have not been included in the calibration process for widely-used models of these currents — although the I Na model by Ebihara and Johnson was incorporated directly into the widely copied INa model by Luo and Rudy (1994). Recently, Lei et al (2020) demonstrated that coupling experimental artefact equations with an I Kr mechanistic model improved predictions.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of experimental artefacts in single-cell studies are well-established, consideration of them while building ion channel and action potential models has been limited (Whittaker et al, 2020). In silico studies investigating series resistance effects on voltage clamp recordings have been done in fast-activating currents, such as I Na and I to (Ebihara and Johnson, 1980; Montnach et al, 2021), but to our knowledge artefact equations have not been included in the calibration process for widely-used models of these currents — although the I Na model by Ebihara and Johnson was incorporated directly into the widely copied INa model by Luo and Rudy (1994). Recently, Lei et al (2020) demonstrated that coupling experimental artefact equations with an I Kr mechanistic model improved predictions.…”
Section: Discussionmentioning
confidence: 99%
“…This flexibility enables neural networks to approximate (almost) any function, making them a powerful universal approximator. However, experimental data are generally imperfect; there are experimental artefacts in the data, for example imperfect series resistance and membrane capacitance compensations, imperfect leak correction, etc., as discussed in Marty and Neher (1995), Sherman et al (1999), Raba et al (2013), Lei et al (2020a,b), and Montnach et al (2021). Unlike (smaller) biophysical models, with limited flexibility, neural networks might easily absorb such undesired, non-biophysical artefacts into the model, hence making non-physiologicallyrelevant predictions.…”
Section: Discussionmentioning
confidence: 99%
“…To control this large variability, a moderate correlation was identified between activation V 1/2 and peak current amplitude in all conditions where peak amplitude ranged beyond 10 nA, such that larger amplitude currents tended to be associated with more hyperpolarized activation V 1/2 values. To ensure that the reported shifts were real and not an artifact of skewed amplitude distributions ( Montnach et al, 2021 ), scatter plots in which V 1/2 values were plotted as a function of their corresponding peak current amplitude were reported. The resulting scatter distribution was then fitted with a line of regression: where V x is the predicted V 1/2 , m is the line slope, A is the maximum current amplitude, and b is the line y-intercept.…”
Section: Methodsmentioning
confidence: 99%